Revisão criminal compulsória em defesa dativa: a dignidade da pessoa humana e a ampla defesa constitucional - Álvares, Silvio Carlos (2008)
The present work is an analysis of the possibility of implantation in our criminal processual legal system, of the inedited institute of the compulsive criminal revision in dative defense. Without any doubt, the Constitution of 1988, post dictatorial regimen, brought a significant change in the life of the Brazilian citizens. Amongst the constitutional principles known as fundamental, we have the human being and dignity the ample defense. The first innovator as expressed principle. The second with bigger intensity, becoming the guarantee and expressed right of any citizen. In the union of both this work was developed. The necessity of the roll of performance of the institute of the Criminal Revision, circumscribed to the hypotheses defined in 1941, with the advance of the social relationships and their consequences, primordially the guarantees and fundamental rights of the citizen, reached by the Federal Constitution suffered a study of enlargement, without losing sight of the exceptional character of such instrument. It justifies the importance of the present work as it defends the interests of the agent condemned in definitive character, based on the human being dignity and in ample defense, having his defense accomplished by court appointed defensor, who is not, obviously, an individual of his personal confidence, since one is nominated by turn. Besides, it does not lose the restrictive character of its applicability in order not to transform itself into an institute of impunity, since it brings expressed requirements, among them, the one that the decision has not been previously reviewed by any kind of ordinary resource